Drivers of Carbon Emissions in Turkey and Indonesia: The Roles of Energy Use, Natural Disasters, and Technological Change - Igunnu, Peter Oluwasegun; Ali , Mumtaz (New Energy Exploitation and Application, 2025)
Switching to renewable energy is key to environmental resilience, especially with the growing problems of fossil fuel dependence and increasing natural disasters. This study looks into how fossil fuel consumption, natural disasters, and adoption of renewable energy technologies affect carbon dioxide (CO2) emissions in Turkey and Indonesia. The analysis is based on the Method of Moments Quantile Regression (MMQR) approach, which captures the heterogeneous effects of these variables across different emission levels. Additionally, Feasible Generalized Least Squares (FGLS) is employed as a robustness check to validate the consistency of the results. The findings show that fossil fuel use contributes to higher CO2 emissions, especially at the lower and middle quantiles. Natural disasters further increase emissions due to the increased energy demand for emergency response and recovery. On the other hand, the expansion of renewable energy leads to consistent and significant reductions of emissions across all levels. These results highlight the need for Turkey and Indonesia to invest in renewable energy infrastructure, implement carbon mitigation policies, integrate disaster risk management in energy planning, and promote innovation in green technologies to achieve long‑term sustainability and environmental protection.